Early Detection of Peripheral Blood Cell Signature in Children Developing Beta-Cell Autoimmunity at a Young Age - Henna Kallionpää; Juhi Somani; Soile Tuomela; Ubaid Ullah; Rafael de Albuquerque; Tapio Lönnberg; Elina Komsi; Heli Siljander; Jarno Honkanen; Taina Härkönen; Aleksandr Peet; Vallo Tillmann; et al. (American Diabetes Association, 2022)
The appearance of Type 1 diabetes (T1D)-associated autoantibodies is the first and only measurable parameter to predict progression toward T1D in genetically susceptible individuals. However, autoantibodies indicate an active autoimmune reaction, wherein the immune tolerance is already broken. Therefore, there is a clear and urgent need for new biomarkers that predict the onset of the autoimmune reaction preceding autoantibody positivity or reflect progressive beta-cell destruction. Here we report the mRNA-sequencing-based analysis of 306 samples including fractionated samples of CD4+ and CD8+ T cells as well as CD4-CD8- cells fractions and unfractionated PBMC samples longitudinally collected from seven children that developed beta-cell autoimmunity (Cases) at a young age and their matched controls. We identified transcripts, including interleukin-32 (IL32) that were upregulated before T1D-associated autoantibodies appeared. Single-cell RNA-seq studies revealed that high IL32 in Case samples were contributed mainly by activated T cells and NK cells. Further, we showed that IL32 expression can be induced by a virus and cytokines in pancreatic islets and beta-cells, respectively. The results provide a basis for early detection of aberrations in the immune system function before T1D and suggest a potential role for IL32 in the pathogenesis of T1D.